2023
DOI: 10.1037/bne0000547
|View full text |Cite
|
Sign up to set email alerts
|

Effect of striatal dopamine on Pavlovian bias. A large [¹⁸F]-DOPA PET study.

Abstract: Interaction between Pavlovian and instrumental control systems is key for adaptive motivated behavior, but also plays an important role in various neuropsychiatric disorders, including depression, addiction, and anxiety. Here, we employed the flouorodopa positron emission tomography ([ 18 F]-DOPA PET) in healthy participants (N = 100) to assess whether dopamine synthesis capacity (K i ), specifically in the ventral striatum, accounts for individual variation in Pavlovian-to-instrumental transfer (PIT). Surpris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…In past studies using the same task, we and others have observed that sometimes participants respond deterministically to a particular Pavlovian / Action Context combination regardless of the instrumental stimulus presented (e.g., Chen et al, 2023). For example, a participant would always make a Go response when a certain appetitive Pavlovian cue was present in an approach context.…”
Section: Deterministic Pit Respondingmentioning
confidence: 87%
“…In past studies using the same task, we and others have observed that sometimes participants respond deterministically to a particular Pavlovian / Action Context combination regardless of the instrumental stimulus presented (e.g., Chen et al, 2023). For example, a participant would always make a Go response when a certain appetitive Pavlovian cue was present in an approach context.…”
Section: Deterministic Pit Respondingmentioning
confidence: 87%
“…Likewise, previous work has linked Pavlovian biases with neuromodulators such as dopamine and serotonin (Boureau & Dayan, 2011;Chen, 2023;Guitart-Masip, Economides et al, 2014;Rutledge et al, 2016), as well as activity in the striatum more generally (Cavanagh et al, 2013). Future work could employ pharmacological and/or neuroimaging methods in order to probe the underlying mechanism of this effect.…”
Section: Transfer Effectsmentioning
confidence: 99%